369 Impact of Early Nutrition on Skeletal Muscle and Adipose Tissue Development. (10th April 2018) - Du, M
Abstract: The fetal stage is critical for animal development because all organs and tissues develop during this stage, which is followed by further development and maturation after birth. The developing tissues and organs are most sensitive to external stresses. Improper early development due to maternal stresses sets the negative trajectory for long-term growth performance of animals. Both muscle and adipose tissue are derived from the dermomyotome during the early embryonic stage. The common origins of muscle cells and adipocytes provide an opportunity to prime myogenic instead of adipogenic differentiation, which is postulated to enhance lean/fat ratio of offspring. The initial formation of muscle fibers starts at the embryonic stage and continues during the fetal stage, while postnatal muscle growth is mainly characterized by hypertrophy of existing muscle fibers, where satellite cells pay a critical role. Thus, increasing muscle fiber number and satellite cell density are two critical control points during early development in order to enhance lean growth. Together with muscle fiber development, adipogenic progenitor cells also starts to form during the embryonic stage, and the differentiation and maturation of adipocytes occurs during fetal and after birth. In addition, different fat depots are not developed at the same time, with intramuscular fat develops later than other fat depots, which provides an opportunity to specifically promote intramuscular adipogenesis with less impacts on other fat depots. Up to now, the impact of maternal over-nutrition and under-nutrition on fetal development and long-term impacts on animal growth performance have been extensively studied, but the impacts of specific nutrients such as vitamins and minerals on fetal development just initiates, with many questions remaining. Understanding these mechanisms will be important for effective and precise management of nutrients provided to dams, in order to promote production efficiency and meat quality of offspring.